Critical Factors in Determining the Success of Government Self-Management Projects: A Case Study Irrigation Water Use Acceleration Program/P3-TGAI - Vero Gusri Vernando; Taufika Ophiyandri; Benny Hidayat; Micky Fetriani (CIVED, 2025)
This research is motivated by the importance of predicting the implementation of a project in the construction field to achieve a success where a project is said to be successful if the project can be completed at a competitive cost, can be completed on time or even faster than the scheduled time, and the quality is achieved. The aim of this study is to determine the critical success factor of government self-management projects (Acceleration Program for Irrigation Water Use Improvement/P3TGAI), so that undesirable things such as cost swells, time delays and others can be predicted as early as possible. This research uses a descriptive method where the populations are community assistance staff (TPM) and Center Management Consultants (KMB) in the program of Acceleration Program for Irrigation Water Use Improvement (P3-TGAI) in the Sumatra V River Basin Center and questionnaires are used as data collection techniques. The results showed that there are 5 determinants of the success of the self-management project for P3-TGAI, such as good communication between parties involved in the project (95.95); appropriate/appropriate work planning (91.89); monitoring of the project by the parties involved (89.19); ability to solve project problems by the parties involved (83.78); proper cost management by the parties involved (83.78). Then, there are 10 aspects that determine the success of P3-TGAI self-management projects, these factors are formed from the highest index in each aspect surveyed.